An Algorithmic Technique for Solving Non-Linear Programming and Quadratic Programming Problems - Das, HK; Hasan, M Babul (GANIT: Journal of Bangladesh Mathematical Society, 2016)
In this paper, we improve a combined algorithm and develop a uniform computer technique for solving constrained, unconstrained Non Linear Programming (NLP) and Quadratic Programming (QP) problems into a single framework. For this, we first review the basic algorithms of convex and concave QP as well as general NLP problems. We also focus on the development of the graphical representations. We use MATHEMATICA 9.0 to develop this algorithmic technique. We present a number of numerical examples to demonstrate our method. GANIT J. Bangladesh Math. Soc.Vol. 35 (2015) 41-55